2007
DOI: 10.1097/scs.0b013e31803052eb
|View full text |Cite
|
Sign up to set email alerts
|

Bone Reconstruction of the Maxillary Alveolus for Subsequent Insertion of a Dental Implant in Patients With Cleft Lip and Palate

Abstract: Bone grafting of maxillary alveolus cleft defect followed by insertion of dental implant may be a good alternative to conventional prosthetic treatment. The principle is the formation of stable alveolar crest with a sufficient three-dimensional volume. The problems are lack and quality of mucoperiosteum for the reconstruction of shell and bone gap characteristics for bone graft intake. The procedure was carried out by a single surgeon (MD) in 45 patients between 29 August 2001 and 30 June 2006, with an 86.7% s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Even though the double-layer membrane was used in those cases, the failure can be blamed on the poor local finding prior to the intervention rather than on the usage of a certain material. 34 …”
Section: Discussionmentioning
confidence: 97%
“…Even though the double-layer membrane was used in those cases, the failure can be blamed on the poor local finding prior to the intervention rather than on the usage of a certain material. 34 …”
Section: Discussionmentioning
confidence: 97%
“…[10][11][12][13] The objectives of bone grafting include providing bony support to the adjacent teeth, facilitating prosthetic restoration, providing bony matrix for tooth eruption into the cleft site, stabilizing the segments, elevating the alar base, eliminating the oronasal fistula, and providing adequate bone volume for implant placement. [11][12][13] It has been reported that the best results are achieved if the graft was done between the ages of 9 to 11 before A B the eruption of the canines. [11][12][13] It has been reported that the best results are achieved if the graft was done between the ages of 9 to 11 before A B the eruption of the canines.…”
Section: Edentulous Cleft Sitementioning
confidence: 99%
“…In addition, the premolar may have to be recontoured into the shape of the cuspid or will require placement of a porcelain veneer. 11,20 Conventional prosthodontics of either a removable partial denture or a fixed prosthesis may be used as a form of tooth replacement. 4,22,25 It has been reported in the literature that positioning the cuspid tooth into the lateral incisor position may predispose the patient to occlusal dysfunction, as well as transversal discrepancy problems and poor aesthetics.…”
Section: Edentulous Cleft Sitementioning
confidence: 99%
“…Such secondary collapse and displacement are often attributed to the “instability” of the disrupted maxillary buttresses 1420 . Correspondingly, maxillae stabilization has always been listed among the major aims of bone graft management for the cleft defect in the literature 3,21 . The extent and pattern of the cleft-related maxillary instability, as well as the effectiveness of bone graft in stabilizing the maxillae, however, have rarely been illuminated 6,12,22,23 .…”
Section: Introductionmentioning
confidence: 99%